A Study of Fuzzy Based Dynamic Load Balancing for Cell Networks - Kaur, Jasween; Kaur, Kiranbir (International Journal of Computer Sciences and Engineering, 2025)
Load balancing is usually a technique used for enhancing the performance of a parallel as well as distributed system. The performance from the systems might be enhanced by means of redistribution regarding load over the different cell phone networks. As a result, load balancing plays a significant role pertaining to increasing your efficiency regarding distributed program, but this is a very challenging and difficult task inside large scale distributed system as the global condition of spread systems is usually changes dynamically. Regarding various factors like greatest throughput, outage possibility, availability along with scalability your distributed program needs productive load evening out. In this paper various load balancing techniques have been studied and out of these dynamic load balancing techniques are seem to be good for load balancing. Also, the present load balancing algorithms are reviewed along with the comparative analysis is usually performed.